The Effect of Transformational Leadership on the Performance of Employees Who Are Intervened by Job Loyalty at the Kutambaru Sub-district Office - Edy Anta Tarigan; Muhammad Isa Indrawan (Yayasan Multidimensi Kreatif, 2024)
The purpose of this study is to find out and analyze the influence of transformational leadership on Employee Performance intervened by Work Loyalty at the Kutambaru District Office. This research was carried out at the Kutambaru District Office. The type of research is quantitative associative. The sample in this study is 15 employees with ASN and honorary status at the Kutambaru District Office. The sampling technique in this study used the entire population of 15 people. The results of the study show that Transformational Leadership has a significant influence on Employee performance as shown by a T-Statistic value of 2.839 > 1.96 and a P Value of 0.012 < 0.05. Transformational Leadership has a significant effect on Employee Work Loyalty with a T-Statistic value of 15.276 > 1.96 with a P-Value of 0.000 < 0.05. Work Loyalty has a significant effect on Employee Performance, this is seen from the results of the T-Statistic value of 2.218 > 1.96 with a P-Value of 0.002 < 0.05. In Indirect Influence, the results show that Work Loyalty has a role as an intervention variable in explaining the relationship between Transformational Leadership and Employee performance. This shows that improvements in Transformational Leadership can increase Work Motivation, which ultimately contributes to improving Employee performance at the Kutambaru District Office.